Using quantitative PCR to identify opportunities to strengthen soil-transmitted helminth control in Solomon Islands: A cross-sectional epidemiological survey - Brandon Le; Naomi Clarke; Sze Fui Hii; Aisling Byrne; Patsy A. Zendejas-Heredia; Susanna Lake; Oliver Sokana; Alam Khattak; Lucia Romani; Daniel Engelman; Titus Nasi; Dickson Boara; et al. (Public Library of Science (PLoS), 2022)
Background The Kato-Katz microscopy technique is the global standard for assessment of soil-transmitted helminth (STH) burden. However, major limitations include its poor sensitivity, requirement for rapid sample processing, and inability to differentiate hookworm species nor detect Strongyloides spp. infections. We assessed the prevalence and intensity of STH species in Solomon Islands by conducting a province-wide survey using quantitative PCR (qPCR) for diagnosis, which can provide much better characterisation of STH burden than microscopy. Methodology/Principal findings We conducted a cross-sectional survey in 18 villages in Western Province to detect infections with six STH species and quantify intensity with three. We used linear mixed model regression to identify potential water, sanitation, and hygiene (WASH) and environmental risk factors for infection. We collected stool specimens from 830 village residents. Overall STH prevalence was 63.3% (range 27.5 to 91.5% across villages), led by Necator americanus (54.5% [range 17.5-89.4%]), followed by Ancylostoma ceylanicum (15.5% [range 2.8-45.8%]), Trichuris trichiura (9.1% [range 0-79.2%]), and Strongyloides spp. (3.2% [range 0-29.2%]). Most infections were of light intensity for N. americanus (85.7%) and T. trichiura (90.7%). Owning a household latrine was associated with a lower risk of N. americanus infection (AOR 0.41, 95% CI 0.24-0.68) while greater precipitation was linked to more common T. trichiura infection (AOR 1.14, 95% CI 1.04-1.25). Conclusion/Significance In this first large-scale population survey of STH in the Pacific using qPCR, we found evidence that ivermectin should be incorporated into STH control programmes because of the presence of T. trichiura and Strongyloides spp., both of which are poorly responsive to albendazole. Furthermore, One Health strategies are needed for improved A. ceylanicum and Strongyloides spp. control, WASH access and use should be improved to complement deworming programmes, and control efforts should ideally be expanded to entire communities. Trial registration ClinicalTrials.gov Australian and New Zealand Clinical Trials Registry ACTRN12618001086257. Author summary Routine assessments of the burden of intestinal worm infections rely on microscopy-based diagnostic methods, such as the Kato-Katz technique. However major limitations include its poor sensitivity, requirement for rapid sample processing, and inability to differentiate individual hookworm species and detect Strongyloides spp. infections. It is important to assess the burden of each of these infections to design control approaches beyond the current core strategy of albendazole preventive chemotherapy. Use of qPCR for diagnosis could address these gaps because it can distinguish all relevant intestinal worm species. We completed a province-wide intestinal worm infections prevalence survey using qPCR in Western Province, Solomon Islands. Overall prevalence was extremely high (62.5%). We identified a high burden of Necator americanus (54.5%) and detected Ancylostoma ceylanicum (15.5%), Trichuris trichiura (9.1%), and Strongyloides spp. (3.2%) infections. Increased age and precipitation were associated with higher prevalence of infection, while owning a household latrine was associated with lower odds of N. americanus infection. Our findings support the need to incorporate ivermectin into deworming programmes for Strongyloides spp. and T. trichiura control as these species are poorly responsive to albendazole, implement One Health strategies to address the zoonotic A. ceylanicum and Strongyloides spp., and expand control efforts to reach entire communities. WASH access should also be improved to complement deworming programmes.